Single Top and Higgs Associated Production in the Minimal B-L Model at the LHC - Bingfang Yang; Zhiyong Liu; Jinzhong Han; Guang Yang (Advances in High Energy Physics)
We study the single top production in association with a Higgs boson in the U(1)B-L extension of the Standard Model at the LHC. We calculate the production cross sections of the processes pp→thX  (h=H1,H2;  X=j,b,W) in this model. We further study the observability of the process pp→tH2j through pp→t(→qq-′b)H2(→4l)j and find that it is still challenging for the 14 TeV LHC with high luminosity to detect this signal.